TINJAUAN YURIDIS KETENTUAN UPAH PEKERJA/BURUH BERDASARKAN UNDANG UNDANG CIPTA KERJA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 168/PUU-XXI/2023 - Puspita, Shinta Novia; Permana, Yana Sukma (Neolectura, 2025)
The Republic of Indonesia as a country of law has stated that National Development is carried out in the context of developing the whole Indonesian people and the development of the entire Indonesian society to create a prosperous, just, prosperous, and equitable society, both materially and spiritually based on Pancasila and the 1945 Constitution. In line with this statement, the Indonesian Government pays serious attention, one of which is in the field of employment. Efforts to provide legal certainty and the implementation of harmonious, dynamic and equitable industrial relations by making laws and regulations and provisions to achieve the goals of industrial relations in Indonesia. Several laws and regulations have been enacted and have even undergone changes, including Law No. 13 of 2003 as the main law on employment, which has now been amended by the Job Creation Law. The latest development has been the enactment of Law No. 6 of 2023 concerning the Stipulation of Government Regulation No. 2 of 2022 concerning Job Creation into Law. Regarding Law No. 6, there has been a Constitutional Court Decision No. 168/PUU-XXI/202. The formulation of the problem in this writing is how to regulate workers' wages after the Constitutional Court Decision Number 168/PUU-XXI/2023. The method used in this writing is Normative Jurisprudence. With the Constitutional Court's decision, the PP regulating Workers' Wages must be immediately made by the government which must accommodate everything related to Workers' Wages.